RANCANG BANGUN PROTOTIP VORTECH (VORTEX TECHNOLOGY) SEBAGAI PEMBANGKIT LISTRIK TENAGA VORTEKS UNTUK KEMANDIRIAN PENERANGAN JEMBATAN SURAMADU - Ghofur, Abdul; Felayati, Frengki Muhamad; Junianto, Sony; Wiradhika, Rizky Akbar; Wiranata, Addien Wahyu; S, Sutarsis (Program Kreativitas Mahasiswa - Karsa Cipta, 2013)
Energy problem is one issue that is important for all developing countries and has been advancing from day to day. As the longest bridge connecting Java and Madura islands, Suramadu Bridge is facing high operational costs, for example it uses fossil fuels as a fuel generator. Given the potential of nature that exist around Suramadu, this study offered a solution to create independence in Suramadu lighting with a vortex energy based tools. The purpose of the program design is to create a Vortech Vortech as a prototype power plant in the vortex for illumination independence Suramadu Bridge.